Ecofeminist Perspective: Climate Change and its Impact on Women - sinaga, cindy adelima; Rahma Hayati Harahap (Journal of Sumatera Sociological Indicators, 2023)
Climate change is one of the environmental issues that continues to be a challenge for global life. The occurrence of climate change has a major impact on the lives of every group of people. This ecological problem has increased gender inequality and gender-based sexual violence in society. In this article, we will discuss further the impact of climate change on women. The method used to conduct research and analysis in this study is to use qualitative research methods to explain the phenomenon. The data were carried out using literature studies using theoretical frameworks. Data collection techniques are carried out by observation and relevant literature studies. Through this article, we will learn how climate change impacts women's groups. The results showed that climate change has an impact on women, especially women in developing countries. The impact of climate change on women can be seen from women's limited access to welfare and impact on women's health access. Declining water quality due to climate change has an impact on women who have the responsibility as the main water provider for household needs. The occurrence of climate change also has an impact on women's health due to water scarcity and pollution.